For this problem, I guess that you problem is solving x from the equation (1). e x-4 e-x = 3 (1) Here is how we do this kind of problem. Let’s do sub. y = e x then we will get 1 y = e-x Hence our equation (1) will become y-4 1 y = 3 (2) Because we know that y = e x 6 = 0, hence we can multiply
This is the end of the preview.
access the rest of the document.
Unformatted text preview: y to the both sides of equation (2), we will get y 2-4 = 3 y (3) And this a quadratical polynomial, you can use the quadratical formula to get y . Then sub. back to get x . [email protected] View